2017
DOI: 10.2147/phmt.s144796
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic prescribing practice in the management of cough or diarrhea among children attending hospitals in Addis Ababa: a cross-sectional study

Abstract: BackgroundIrrational use of antibiotics is a global problem. Failure to follow clinical guidelines is one of the main reasons for irrational use of antibiotics. Cough and/or diarrhea are the main childhood illnesses in Ethiopia, and health care providers are expected to follow the national guideline while managing these illnesses. This study tried to assess the extent of adherence to the guideline while managing cases of childhood diarrhea and/or cough.MethodsThe study was conducted in 23 hospitals in Addis Ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 8 publications
1
13
0
1
Order By: Relevance
“…In comparison, respondents from a study in developed countries showed lesser confidence in planning the duration of antibiotic treatment, or selection of more than one antibiotic for a combination therapy, than choosing the right antibiotic . An overly high confidence in the use of antibiotics without adequate knowledge on local antibiotic resistance patterns, especially when coupled with difficulty in choosing the correct antibiotic, could be one reason for the high rates of inappropriate antibiotic prescribing in developing countries, as shown by a recent study in Ethiopia, where most of the prescribed antibiotics were not in accordance with national guidelines and most of these inappropriate prescriptions were not required …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison, respondents from a study in developed countries showed lesser confidence in planning the duration of antibiotic treatment, or selection of more than one antibiotic for a combination therapy, than choosing the right antibiotic . An overly high confidence in the use of antibiotics without adequate knowledge on local antibiotic resistance patterns, especially when coupled with difficulty in choosing the correct antibiotic, could be one reason for the high rates of inappropriate antibiotic prescribing in developing countries, as shown by a recent study in Ethiopia, where most of the prescribed antibiotics were not in accordance with national guidelines and most of these inappropriate prescriptions were not required …”
Section: Discussionmentioning
confidence: 99%
“…32 An overly high confidence in the use of antibiotics without adequate knowledge on local antibiotic resistance patterns, especially when coupled with difficulty in choosing the correct antibiotic, could be one reason for the high rates of inappropriate antibiotic prescribing in developing countries, as shown by a recent study in Ethiopia, where most of the prescribed antibiotics were not in accordance with national guidelines and most of these inappropriate prescriptions were not required. 39 TA B L E 2 Commonly used guide when prescribing antibiotics The reported variation in what the respondents use to guide their antibiotic prescribing and the recommendations highlighted to improve antibiotic prescribing could probably be explained by the differences in the available services in the different settings, or problems with their acceptability, local guidelines versus international guidelines for example. 15,17 Thus, the use of local guidelines or advice from experts such as pharmacists may not be available in all settings which could have therefore led to their more limited report by the studies.…”
Section: Discussionmentioning
confidence: 99%
“…Although infectious diseases are more common in developing countries, such as Pakistan, due to poor hygienic condition of hospitals, the surgeons usually overprescribe broad spectrum antibiotics which may add to the burden of AMR [40]. A study done in Ethiopia where national antibiotic prescription guidelines were mostly not followed showed that lack of the knowledge of local resistance patterns is probably the reason for injudicious antibiotic prescription pattern seen in the developing world, [41].…”
Section: Plos Onementioning
confidence: 99%
“…Typical features of prescribing in LMICs include high volumes of antibiotic prescribing [16], although these higher levels can be partially linked to greater burden of infectious diseases [17]. Prescribing in LMICs has also been characterized by high empirical use of broad-spectrum antibiotics [8,18,19], non-availability of and/or poor compliance with treatment guidelines [20] and limited use of diagnostic tests [21].…”
Section: Introductionmentioning
confidence: 99%